Sequencing of the chicken non-erythroid spectrin cDNA reveals an internal repetitive structure homologous to the human erythrocyte spectrin. - Wasenius, V M (1985)
Immunological screening of a chicken gizzard cDNA expression library was used to isolate two clones encoding a part of the non-erythroid spectrin-like protein. Clones were identified by immunoblotting of the polypeptides synthesized in Escherichia coli cells transformed with cDNA cloned in the pUC8 plasmid vector using polyclonal rabbit antibodies raised against bovine non-erythroid spectrin. The sequence of an approximately 1.5-kb cDNA insert of one clone was determined. Analysis of the predicted amino acid sequence reveals that, despite differences in immunological cross-reactivity and peptide maps, the chicken non-erythroid and the human erythrocyte spectrins are highly homologous proteins. Like the human erythrocyte spectrin, the chicken smooth muscle spectrin appears also to be constructed from repeated, homologous structures of 106 amino acid residues. This is probably a universal structure motif of spectrins.